Peran Kepemimpinan Kepala Sekolah dalam Optimalisasi Standar Guru di Sekolah Islam Terpadu - Alimin, Alimin; Citriadin, Yudin (FKIP Universitas Mataram, 2024)
This research aims to explore the leadership role of the Principal in improving teacher professionalism at SMPIT Bukit Quran Nusantara Mataram, with a focus on implementing the qualification standards for Integrated Islamic School teachers. Using a qualitative approach and descriptive field research design, this research collected primary data from interviews with ten respondents—a school principal and nine teachers—as well as secondary data from various related documents. The research results show that a minimum academic qualification of Bachelor's degree, involvement in Islamic Personal Development (BPI), and memorizing the Al-Qur'an are essential qualifications maintained by the Principal to increase teacher professionalism. In addition, the Principal participates in developing teachers' pedagogical, professional, social and social piety competencies through regular training and reflection, which supports the achievement of quality education based on Islamic values. The data analysis technique used is an interactive model which involves data reduction, data presentation and drawing conclusions to ensure the validity of the research results.